Assessment of Dysmenorrhea and its Associated Factors among Females of District Ghaziabad - Verma, Priyanka; Gupta, Gajendra K; Singh, Anupama; Agrawal, Deepika; Nawaz Zaidi, Syed Hasan; Abhishek (National Journal of Community Medicine, 2024)
Background: Dysmenorrhea is a very common problem and a large number of females in our society are suffering from it. This study aims to determine the prevalence of dysmenorrhea and its associated lifestyle and other factors. Methodology: This was a cross-sectional study which was conducted among females aged between 15 to 45 years in urban population of district Ghaziabad through a house-to-house survey, using a pre-designed, semi-structured questionnaire. Results: The prevalence of dysmenorrhea was 67.8%. Out of the participants having dysmenorrhea, 36.5% females were experiencing mild pain, 44.3% were experiencing moderate pain and 19.1% were experiencing severe pain. The chances of dysmenorrhea were significantly more in participants of 15 to 25 years of age, participants who had attained early menarche, those having pre-menstrual symptoms and those who had passage of clots during menstruation, participants consuming refined flour, fried food, preservatives, soda and those who were skipping meals. Participants doing physical exercises showed less chance of menstrual pain. Conclusions: The prevalence is dysmenorrhea is quite high in our society. It may be related to factors which are modifiable, such as diet and exercise. An improvement of lifestyle is recommended.